The equation of line going through points (-4, 0) and (0, 3) is [tex]y = \frac{3}{4}x + 3[/tex]
Given that line above goes through points (-4,0) and (0,3)
To find: equation of line
The equation of line passing through two points [tex](x_1 , y_1)[/tex] and [tex](x_2, y_2)[/tex] is given as:
[tex]y - y_1 = m(x - x_1)[/tex]
Where "m" is the slope of line
The slope of line is given as:
[tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
Here for the given points (-4, 0) and (0, 3) we have:
[tex]x_1 = -4 ; y_1 = 0 ; x_2 = 0 ; y_2 = 3[/tex]
Substituting the given values in slope formula,
[tex]m=\frac{3-0}{0-(-4)}=\frac{3}{4}[/tex]
Thus slope of line [tex]m = \frac{3}{4}[/tex]
Now substitute "m" into equation of line
Thus the required equation of line is:
[tex]y - y_1 = m(x - x_1)\\\\y - 0 = \frac{3}{4}(x - (-4))\\\\y = \frac{3}{4}(x + 4)\\\\y = \frac{3}{4}x + 3[/tex]
Thus the required equation of line is found